Metazoan diversity and seasonality through eDNA metabarcoding at a Mediterranean long-term ecological research site. (16th April 2021) - Di Capua, Iole; Piredda, Roberta; Mazzocchi, Maria Grazia; Zingone, Adriana
Abstract: Metabarcoding of environmental DNA has provided striking insights into marine microbial diversity. With this approach, we assessed the diversity of metazoan assemblages and their temporal variations at the Long-Term Ecological Research site MareChiara (LTER-MC) in the Gulf of Naples (Mediterranean Sea). The Illumina sequencing of the V4-18S rRNA fragment from 48 surface samples collected from 2011 to 2013 produced a total of 5 011 047 marine metazoan reads. The normalized dataset was generally dominated by copepods (60.3%), followed by annelids (34.7%) mostly represented by the invasive benthic polychaete Hydroides elegans . Non-copepod holoplankton was mainly represented by siphonophores, rotifers, and appendicularians, with occasional mass occurrences of jellyfish. The rest of meroplankton (mainly molluscs, annelids, and anthozoans) showed a high diversity, covering all 11 zooplankton phyla, from Porifera to Craniata. A high number of copepod genera were identified, with seasonal recurrence matching patterns observed in 30 years of studies in the Gulf of Naples. Despite limitations related to the molecular marker resolution and reference dataset, the study provided valuable insights into diversity and seasonal patterns of the whole metazoan assemblage, expanding the knowledge on rare or hardly identifiable taxa and confirming DNA metabarcoding as a powerful approach to be integrated at LTER sites.